NURSING ASSISTANCE TO THE PATIENT WITH PENIS CANCER - da Silva Norberto, Damiana; Eduarda Almeida de Souza, Cicera; Silva Oliveira, Geane; Caroline de Souza, Anne; do Nascimento Andrade Feitosa, Ankilma (Health and Society, 2022)
INTRODUCTION: Penile cancer is considered an aggressive disease that can cause penile lesions and even organ loss, affecting men’s quality of life. In this bias, nursing works with guidelines on prevention and appropriate treatment for the patient affected by this neoplasm. OBJECTIVE: To carry out a bibliographic survey on the role of nursing in guiding the prevention of penile cancer and the care provided to the patient. METHODOLOGY: This is an integrative literature review carried out in the Virtual Health Library (VHL) database. The present study has as its guiding question: what is the role of nurses in nursing care for patients with penile cancer? The articles will be collected between August and September 2022, using the descriptors: Nursing, Penile Neoplasms and Men’s Health. The inclusion criteria used will be: full articles available in full; published between the years 2018 and 2022, that is, with a time interval of 05 years; full text available in Portuguese. Exclusion data will be: Duplicate articles, reviews, monographs, theses, books, abstracts in proceedings, dates retrograde to required and incomplete documents. EXPECTED RESULTS: It is expected to describe the main actions performed by nurses to clients affected by penile cancer.